KESALEHAN SOSIAL MELALUI PENDIDIKAN FILANTROPI ISLAM - Fauzi al-Mubarok; Ahmad Buchori Muslim Buchori Muslim (STIT Islamic Village Tangerang, 2020)
The balance between spiritual piety and social righteousness is a religious order of Islam, both the teachings listed in the Qur'an, as well as in the Hadith Rasulullah SAW. And among one of the social piety is to give the philanthropy of Islam, this is as a form of gratitude for the gift of sustenance given by Allah SWT to philanthropists, as well as his sense to fellow Muslims in hopes can Relieve their life burden. The righteous philanthropist will carry out the commandment of God and his apostle with sincerity and full of consciousness that wealth and wealth so as not to continue to spin around the rich man alone, therefore with the Islamic philanthropy of wealth and wealth can Enjoyed the results by Fakir, poor, Dhuafa, orphans, and who are entitled to receive it to improve their welfare in the field of economics, health and education. Spiritual righteousness and social righteousness need to be established early on perhaps through education and teaching conducted in primary and secondary schools. These two forms of righteousness are like two currencies that cannot be separated from each other, so that the righteous are spiritually more grounded and influential in the surrounding environment.